Lipoid proteinosis in two siblings - Behera Samira Kumar; Nayak Surajit; Debi Basanti; Sahu Antaryami; Mishra Debiprasad (Wolters Kluwer Medknow Publications, 2006)
Lipoid proteinosis denotes a rare autosomal recessive disorder. We report here lipoid proteinosis in a 31-year-old unmarried female along with her sibling. She had hoarseness of voice along with multiple asymptomatic warty papules over face, neck and extremitis with similar findings in one of her siblings. Laryngoscope showed beaded deposits over epiglottis and vocal cords of both patients. Biopsy showed PAS-positive homogeneous eosinophilic materials in upper dermis.